2019
DOI: 10.1111/andr.12581
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like factor 3, luteinizing hormone and testosterone in testicular cancer patients: effects of β‐hCG and cancer treatment

Abstract: Background: Primary hypogonadism (low testosterone and high luteinizing hormone, LH) is present in approximately 20% of testicular cancer (TC) survivors after orchidectomy with or without chemotherapy. Objectives: We investigated insulin-like factor 3 (INSL3), a novel marker of Leydig cell function, in TC patients. Materials and Methods: We analyzed: (I) a cross-sectional cohort of TC patients after orchidectomy with or without chemotherapy (1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…These results showed that in chemotherapy‐treated TC patients, gonadal endocrine function was disturbed pre‐chemotherapy, one year after, and at long‐term follow up …”
Section: Testicular Cancermentioning
confidence: 77%
See 4 more Smart Citations
“…These results showed that in chemotherapy‐treated TC patients, gonadal endocrine function was disturbed pre‐chemotherapy, one year after, and at long‐term follow up …”
Section: Testicular Cancermentioning
confidence: 77%
“…In the longitudinal cohort, TC survivors with normal β‐hCG levels (≤5mU/L, n=35) pre‐chemotherapy had increased LH levels one year after chemotherapy versus their pre‐chemotherapy levels ( p =0.001) but no change in testosterone or INSL3. In contrast, TC survivors with high β‐hCG levels pre‐chemotherapy (n=35) had decreased LH, markedly raised testosterone, and low ISNL3 levels pre‐chemotherapy, but increased LH, decreased testosterone and increased INSL3 levels one year later ( p <0.001 for all) …”
Section: Testicular Cancermentioning
confidence: 95%
See 3 more Smart Citations